The Clinical Case for the Integration of a Ketone Sensor as Part of a Closed Loop Insulin Pump System. (September 2019) - Lee, Melissa H.; Paldus, Barbora; Krishnamurthy, Balasubramanium; McAuley, Sybil A.; Shah, Rajiv; Jenkins, Alicia J.; O'Neal, David N.
Closed loop (CL) systems deliver insulin with a rapid onset and offset in action. Although favorable overall, the absence of a long-acting insulin increases the risk of diabetic ketoacidosis (DKA) which can occur with insulin delivery failure, acute illness, low carbohydrate diets, sodium glucose-linked transporter inhibitors, and high intensity exercise. A CL system relying entirely on interstitial glucose measurements may not provide an alert for DKA and many people with type 1 diabetes (T1D) do not carry a blood ketone meter and test-strips. Ketone sensing is theoretically feasible. A multianalyte platform incorporating a ketone sensor could provide an additional CL input without an increase in burden for the person with T1D, warning of impending DKA to allow remedial action to be taken. We outline the clinical case for inclusion of continuous ketone sensing as part of future CL systems.